Removal of nitrate and ammonium ions from livestock wastewater by hybrid systems composed of zero-valent iron and adsorbents - Ji, Min-Kyu; Ahn, Yong-Tae; Khan, Moonis Ali; Abou-Shanab, Reda A. I.; Cho, Yunchul; Choi, Jae-Young; Kim, Yong Je; Song, Hocheol; Jeon, Byong-Hun (TAYLOR & FRANCIS LTD, 2011)
The feasibility of hybrid systems for simultaneous removal of nitrate (NO3-) and ammonium ions (NH4+) from livestock wastewater was examined in batch experiments. As a part of efforts to remove nitrate and ammonium simultaneously, Fe-0 and adsorbents including coconut-based granular activated carbon (GAC), sepiolite and filtralite were used. Various parameters such as adsorbent dosages and temperature were studied. Removal of NO3- increased with increase in temperature. Maximum NO3- removal (85.3%) was observed for the Fe-0-filtralite hybrid system at 45 degrees C for a 24 h reaction time. Increase in GAC and sepiolite dosages had significant (P < 0.01) effect on the NH4+ removal efficiency, which was primarily due to the net negative surface charge of the adsorbents. The efficiency of hybrid systems for the removal of NO3- was in the order of filtralite > sepiolite > GAC, and the order of the removal of NH4+ was GAC > sepiolite > filtralite. The results of the present study suggest that the use of hybrid systems could be a promising innovative technology for achieving simultaneous removal of NO3- and NH4+ from livestock wastewater.
Keywords: AQUEOUS-SOLUTION; GREEN RUSTS; REDUCTION; ADSORPTION; PH; HYDROXYSULPHATE; SEPIOLITE; PRODUCTS; LEACHATE; DYES